2013
DOI: 10.3389/fnins.2013.00098
|View full text |Cite
|
Sign up to set email alerts
|

Is it stress? The role of stress related systems in chronic food restriction-induced augmentation of heroin seeking in the rat

Abstract: Drug addiction is a chronic disease characterized by recurring episodes of abstinence and relapse. The precise mechanisms underlying this pattern are yet to be elucidated, but stress is thought to be a major factor in relapse. Recently, we reported that rats under withdrawal and exposed to a mild chronic stressor, prolonged food restriction, show increased heroin seeking compared to sated controls. Previous studies demonstrated a critical role for corticotropin-releasing factor (CRF) and corticosterone, hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
1
14
1
Order By: Relevance
“…In addition, it is unknown whether the facilitating effects of chronic stress exposure on incubated craving are observed for drugs other than heroin (D’Cunha et al 2013; Sedki et al 2013, 2015) and cocaine (current results). Since the incubation model is relevant to understanding persistent vulnerability to relapse (i.e., Reichel & Bevins, 2009; Pickens et al 2011) and incubation has been shown to occur in human users of several drugs including cocaine (Bedi et al 2011; Wang et al 2013; Li et al 2014; Parvaz et al 2016), further characterizing these effects will help to identify more effective strategies with which to treat craving and relapse in recovering addicts.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In addition, it is unknown whether the facilitating effects of chronic stress exposure on incubated craving are observed for drugs other than heroin (D’Cunha et al 2013; Sedki et al 2013, 2015) and cocaine (current results). Since the incubation model is relevant to understanding persistent vulnerability to relapse (i.e., Reichel & Bevins, 2009; Pickens et al 2011) and incubation has been shown to occur in human users of several drugs including cocaine (Bedi et al 2011; Wang et al 2013; Li et al 2014; Parvaz et al 2016), further characterizing these effects will help to identify more effective strategies with which to treat craving and relapse in recovering addicts.…”
Section: Discussionmentioning
confidence: 79%
“…The Shalev laboratory has studied the effects of chronic stress in rats that undergo extended-access heroin self-administration followed by forced abstinence (without extinction training). Their results show that chronic mild food restriction stress (weight maintained at 90% of baseline weight) in male rats during the first two weeks of withdrawal (WD2-WD15) from heroin self-administration produces a robust increase in cue-induced heroin seeking on WD15 compared to non-food restricted controls (D’Cunha et al 2013; Sedki et al 2013). This is due to chronic food restriction, as a shorter (3–5 day) food restriction period did not enhance heroin seeking (D’Cunha et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This review shows that ghrelin universally enhances sensitivity to psychostimulants and that ghrelin receptor antagonism may be an important therapeutic target to help quit smoking and curb addictive behaviors. Ghrelin may also be implicated in the narcotic drug seeking following stress, given that, as shown by Sedki et al (2013), blocking CRF receptors or adrenalectomy do not attenuate the effects of food restriction on heroin seeking behavior.…”
mentioning
confidence: 99%